Impact of environmental toxicity on health in ayurvedic parlance - Gopalakrishna Pillai, Resmi Bhuvaneswari; Yadav, Chhaju Ram; Mangampadath, Abhilash (International Journal Of Community Medicine And Public Health, 2022)
Environmental toxicity is being increased tremendously and its impact on health is unavoidable. Though many remedial measures are being taken, some serious call for action globally should be taken to make the efforts effective. In Ayurveda significant place has been given for environmental health as its fundamental principle itself relies on the fact that only a healthy environment can help in healthy living of the beings as both are inseparable units co-existing in a complementing manner. The extent of pollution was far less during the period when classical texts of Ayurveda were written, considerable value had given even then for the environmental health. Also, in order to reduce the toxicity of environment and to lighten the burden of ill-effects of environmental toxicity many remedial measures have been advocated. The classical Ayurveda texts and articles available in online databases dealing with the concerned subject were reviewed. The toxicity endorsed by the environmental factors could be prevented to a great extent by resorting to the diet and regimen prescribed by Ayurveda, if symptoms already manifested could be managed by the medications and recommendations given in Ayurveda. Prime focus should be on the status of agni and to restore the metabolism in an optimal level so that the health could be maintained. The preventive as well as curative methods advocated in Ayurveda in limiting the ill-effects of environmental toxicity which has been proven through studies have been discussed here. Transition is nearly inevitable and the necessity to be adapted to the changing environmental conditions is very important. By adopting the daily regimen, seasonal regimen, panchakarma (the five purificatory procedures) and rasayana (rejuvenative) therapy, usage of nitya rasayana (daily admissible revitalizers) along with proper code of conduct (sadvrutta and achara rasayana) will definitely help to reduce the infliction of toxic effects of environmental pollution.